The Relationship Between Bureaucratic Leadership, Organizational Agility and Organizational Performance in the Tax Sector - Wijaya, Sutirja; Ningrum, Sinta; Myrna, Rita; Karlina, Nina (KnE Social Sciences, 2022)
The demands on public organizations increasingly place leaders in complex situations. Leaders are required to be able to unravel the complexity of the organization and deal with various problems, both internal and external. The leadership role necessitates responding and being proactive. The purpose of this research was to analyze the relationship between bureaucratic leadership, organizational agility and organizational performance in the tax sector. This research involved an explanatory survey by the SAMSAT office in Banten Province, conducted with 238 participants who were members of the public and regional tax officials who were randomly selected without differentiating positions in management. The variant SEM procedure was used for data analysis. The findings showed that the demands of bureaucratic leadership in the digital era are very high. Acceleration is an important aspect inherent in leadership in the digital era. Control over changes in local politics and administration, and demands for acceleration, necessitate leaders who have capacity. Bureaucratic leadership has an influence on organizational agility and organizational performance in the tax sector. Bureaucratic leadership influences organizational performance either directly or through organizational agility. The theoretical implication is the need to develop the concept of leadership in the context of the digital era in order to encourage public performance. The practical implication is the need for leadership that is agile in responding to public demands and acts quickly by integrating administrative orientation, understanding local political dynamics and being ready to face acceleration challenges. Keywords: bureaucratic leadership, organizational agility, organizational performance, the taxation sector